Rational use of drugs to alleviate adverse outcomes caused by COVID-19 quarantine in women with intrahepatic cholestasis of pregnancy - Cai, Qin-Yu; Li, Xia; Yang, Yin; Luo, Xin; Luo, Shu-Juan; Xiong, Jing; He, Zong-Yan; Chen, Yuan; Mou, Yi-Wei; Hu, Ji-Yuan; Yang, Shu; Lan, Xia; et al. (Frontiers in Medicine, 2023)
Purpose: To investigate the impacts of home quarantine on pregnancy outcomes of women with intrahepatic cholestasis of pregnancy (ICP) during the COVID-19 outbreak and whether rational use of drugs will change these impacts.This multi-center study was conducted to compare the pregnancy outcomes in women with ICP between the home quarantine group and the non-home quarantine group in southwest China. Propensity score matching (PSM) was performed to confirm the pregnancy outcomes of the medication group and the non-medication group in women with ICP during the epidemic period.Results: A total of 3161 women with ICP were enrolled in this study, including 816 in the home quarantine group and 2345 in the non-home quarantine group. Women with ICP in the home quarantine group had worse pregnancy outcomes, such as a growing risk of gestational diabetes mellitus A1, fetal growth restriction (FGR), pre-eclampsia, preterm delivery, and even stillbirth. Drug therapy could alleviate some adverse pregnancy outcomes caused by home quarantine, including pre-eclampsia, preterm delivery, and meconium-stained amniotic fluid.Conclusions: COVID-19 quarantine would increase the incidence of ICP and lead to adverse pregnancy outcomes in women with ICP. The rational use of drugs reduced some obstetrical complications and improved partial pregnancy outcomes. Our findings suggested that the government and hospitals should enhance their management and life guidance for women with ICP and speed up developing home quarantine guidelines.